Financial Inclusion Services, Women Financing Schemes, and the Growth of Women-Owned SMEs - Nyume Nyingmeh, Blaise; Kongnyuy Mainimo, Leo (Technium Social Sciences Journal, 2026)
This study examined the relationships among financial inclusion services, women’s financing schemes, and the growth of women-owned small and medium-sized enterprises (SMEs) at the base of the pyramid in Cameroon. A quantitative cross-sectional survey was conducted with 385 women entrepreneurs operating legally registered SMEs in Cameroon. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software to test direct and mediated relationships. The study employed a two-stage approach to model women’s empowerment as a second-order construct comprising financial and non-financial services, grounded in the Resource-Based View. Findings revealed that financial services had a significant positive effect on SME growth (β = 0.428, p < 0.001), whereas non-financial services had a significant negative effect (β = -0.159, p = 0.029). Women’s financing schemes showed no significant effect on growth (β = -0.001, p = 0.992). Most critically, women’s financing schemes negatively mediated the relationship between women’s empowerment and SME growth (β = -0.115, p = 0.044), indicating that channelling women through gender-targeted programs undermines rather than enhances the positive effects of financial inclusion. The cross-sectional design limits causal inference, and the study focuses exclusively on Cameroon, which may limit generalizability. The study suggests that well-intentioned gender-targeted financing schemes may inadvertently trap women entrepreneurs in lower-performing trajectories, reinforcing rather than reducing gender gaps in entrepreneurial performance. Redirecting resources toward removing discriminatory barriers in mainstream financial markets could better promote women’s economic empowerment.